PENGARUH PENILAIAN KERJA, KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI PADA PT BANK NEGARA INDONESIA (PERSERO) TBK CABANG UNDIP SEMARANG - Christine Natalia Gultom; Saryadi Saryadi; Sendhang Nurseto (Universitas Diponegoro, 2015)
Email: christinegultom23@gmail.comAbstract: Human resources has a very important role in the company, because humanresources is an important key in empowering other resources. The success of a company inachieving its objectives can’t be separated from human resources. Because resourcesprovide an important role, the company always strives to be able to allocate substantialfunds to improve human resources. In the situation of banking competition, banks need agreat effort, then one effort is to further improve the performance of employees optimally.So that the objectives set by the company achieved well. The purpose of this research wasto determine whether there is influence appraisal, compensation to employee performancethrough motivation at PT. Bank Negara Indonesia (Persero), Tbk Branch Undip Semarang.The population in this study were all employees' fixed numbering 70 people, so this studyuses census research. The analytical tool used in this research is simple regression,regression, and path. Results of analysis and hypothesis testing showed that job appraisal,compensation, and motivation have an impact on employee performance. Judging from thecalculation of the regression coefficients indicate that job appraisal, compensation,motivation is able to explain the variable performance of the employee, where the results ofthe regression coefficient has an influence appraisal of 0.279, compensation of 0.022, andthe motivation of 0.76 to employee performance. This shows that the assessor job has agreater impact and has a strong degree of closeness of relationship to employeeperformance. Thus we can conclude the influence appraisal, compensation to employeeperformance through motivation at PT. Bank Negara Indonesia (Persero), Tbk BranchUndip Semarang. Advice can be given in this study and the need to increase attention tocompensation and motivation can be done by paying attention to the results of the work,can be in the form of bonuses from employers so that employees are encouraged to workoptimally.